Evidence for a core-shell structure of hydrothermal carbon. (May 2020) - Higgins, Luke J.R.; Brown, Andy P.; Harrington, John P.; Ross, Andrew B.; Kaulich, Burkhard; Mishra, Bhoopesh
Abstract: Hydrothermal carbonisation (HTC) has been demonstrated to be a sustainable thermochemical process, capable of producing functionalised carbon materials for a wide range of applications. In order to better apply such materials, the local chemistry and reaction pathways governing hydrothermal carbon growth must be understood. We report the use of scanning transmission X-ray microscopy (STXM) to observe chemical changes in the functionality of carbon between the interface and bulk regions of HTC. Spatially-resolved, element-specific X-ray photo-absorption spectra show the presence of differing local carbon chemistry between bulk "core" and interface "shell" regions of a glucose-derived hydrothermal carbon spherule. STXM provides direct evidence to suggest that mechanistic pathways differ between the core and shell of the hydrothermal carbon. In the shell region, at the water-carbon interface, more aldehyde and/or carboxylic species are suspected to provide a reactive interface for bridging reactions to occur with local furan-based monomers. In contrast, condensation reactions appear to dominate in the core, removing aryl-linking units between polyfuranic domains. The application of STXM to HTC presents opportunities for a more comprehensive understanding of the spatial distribution of carbon species within hydrothermal carbon, especially at the solvent-carbon interface. Graphical abstract: Image 1